Brown, Archie: The Human Factor. Gorbachev, Reagan, and Thatcher, and the end of the Cold War. Oxford, Oxford UP, 2020, 500pp. - Velasco Martínez, Luis (Revista del Instituto Español de Estudios Estratégicos, 2021)
Reseña de: Brown, Archie: The Human Factor. Gorbachev, Reagan, and Thatcher, and the end of the Cold War. Oxford, Oxford UP, 2020, 500pp.